2010
DOI: 10.1002/anie.201003300
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Asymmetric 1,4‐Addition of Aryl Alanes to Trisubstituted Enones: Binap as an Effective Ligand in the Formation of Quaternary Stereocenters

Abstract: All for one and 1,4-all: Readily available aryl alanes are used in the rhodium-catalyzed asymmetric conjugate addition reaction with a variety of cyclic and acyclic enones. The enhanced reactivity of the system allows the use of the common binap ligand for the generation of quaternary benzylic stereocenters in excellent enantioselectivity (see scheme)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…As described by Shintani and Hayashi, a significant expansion in scope is associated with the use of chiral diene ligands XXIV and XXV , which enable arylation of β,β-disubstituted unsaturated ketones and esters using tetraarylborates , as well as arylboroxines . Woodward and Alexakis found that more reactive arylaluminum reagents could be applied to similar Rh-catalyzed transformations using the more common ligand BINAP (not shown) . A related palladium-catalyzed conjugate addition of arylboronic acids to acyclic enones was reported, but enantioselectivities were quite low (not shown) …”
Section: Acyclic Quaternary Carbon Stereocentersmentioning
confidence: 99%
“…As described by Shintani and Hayashi, a significant expansion in scope is associated with the use of chiral diene ligands XXIV and XXV , which enable arylation of β,β-disubstituted unsaturated ketones and esters using tetraarylborates , as well as arylboroxines . Woodward and Alexakis found that more reactive arylaluminum reagents could be applied to similar Rh-catalyzed transformations using the more common ligand BINAP (not shown) . A related palladium-catalyzed conjugate addition of arylboronic acids to acyclic enones was reported, but enantioselectivities were quite low (not shown) …”
Section: Acyclic Quaternary Carbon Stereocentersmentioning
confidence: 99%
“…The steric congestion around a b,b-disubstituted olefin prevents 1,4addition, but favors 1,2-addition, and the chiral catalyst hardly recognizes the enantioface because of the similarity of substituents on an olefinic carbon atom ( Figure 1). [5] Asymmetric addition reactions for the construction of a chiral quaternary carbon center have been developed extensively, but the alkylation remains a challenging transformation. Hayashi and co-workers reported the rhodium-catalyzed asymmetric conjugate addition of organoboron compounds to a,b-unsaturated esters and enones with an excess amount of Ar 4 BNa or organoboroxine under thermal conditions, with enones typically providing lower enantioselectivity.…”
mentioning
confidence: 99%
“…[3] There have been only a few reports on the construction of a chiral quaternary carbon center by the conjugate addition of organometallic reagents to acyclic activated olefins. [5] Asymmetric addition reactions for the construction of a chiral quaternary carbon center have been developed extensively, but the alkylation remains a challenging transformation. [4] Alexakis, Woodward, and co-workers reported the rhodium-catalyzed asymmetric addition of PhAlMe 2 to b,b-disubstituted enones and the yields were moderate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially,wefocused on the reaction between dimethyl-ptolylaluminum (1a,e asily prepared from p-tolyllithium and dimethylaluminum chloride) [14] and 2-iodonaphthalene (2a). After extensive studies, [15] we identified the optimum conditions for direct coupling to be heating at 110 8 8CinTHF.W e then examined the scope and limitations of the cross-coupling reaction between various aryl aluminum compounds 1 and aryl iodides 2 (Scheme 1).…”
mentioning
confidence: 99%